Is there a resource curse in Timor-Leste? A critical review of recent evidence. Issue 1 (1st January 2020) - John, Samuel; Papyrakis, Elissaios; Tasciotti, Luca
ABSTRACT: Shortly after oil production commenced in 2004, Timor-Leste became one of the most oil dependent countries in the world. The purpose of this piece is to assess whether Timor-Leste has been suffering from the typical political and economic ailments associated with the 'resource curse' hypothesis. The study critically analyses available evidence with reference to some of the common manifestations of the resource curse: conflict, rent-seeking behavior, Dutch disease and revenue volatility. It confirms that all of the examined mechanisms of the resource curse are present in Timor-Leste to varying degrees. This does not necessarily point to a causal relationship between mineral dependence and these socio-economic problems. Many of these problems, common amongst developing countries, are attributed to a wide array of historical and political factors (which are likely to be associated with colonialism and inherited weak governance structures). While it might be tempting to attribute these problems to mineral discoveries and related income shocks, careful examination suggests that the extractive sector exacerbates pre-existing problems than necessarily causes them.